1995
DOI: 10.1097/00000542-199507000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continuous Arteriovenous Hemofiltration Combined with Systemic Vasopressor Therapy on Depressed Left Ventricular Contractility and Tissue Oxygen Delivery in Canine Escherichia coli Sepsis

Abstract: Our study offers a rationale for the combined use of phenylephrine and CAVH in the reversal of cardiac depression and hypotension in sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The possibilities for the lack of hemodynamic improvement despite removal of FCS activity from plasma could be related to a number of factors. Since we previously showed that myocardial depression in sepsis could be acutely reversed by CAVH [4,13], the binding of the FCS to the myocardial cell must be somewhat reversible. However, the time course of events that occurs once FCS is bound to the myocardial cell is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The possibilities for the lack of hemodynamic improvement despite removal of FCS activity from plasma could be related to a number of factors. Since we previously showed that myocardial depression in sepsis could be acutely reversed by CAVH [4,13], the binding of the FCS to the myocardial cell must be somewhat reversible. However, the time course of events that occurs once FCS is bound to the myocardial cell is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…In those groups in which hemofiltration was performed, the right femoral artery and vein were cannulated with polyethylene catheters for connection to a hemofilter (Gambro, CAVH Kit FH66, Hechingen, Germany) [4,13]. The hemofilter permits all solutes up to a molecular mass of approximately 30 000 Da to be removed from the plasma.…”
Section: Animal Preparation and Hemodynamic Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect on cardiac function was demonstrated once again by Mink et al and the effect attributed to the removal of circulating substances with a molecular weight of less than 30,000 Da. [58] These results have been repeatedly proven in subsequent studies [59] that confi rmed the elimination of different molecules. [60][61][62][63][64] Yekebas et al [64][65][66] in a series of experiments based in a model of pancreatitis in pigs allocated subjects to different levels of intensity of hemofi ltration plus adsorption and were able to demonstrate an improvement in serum cytokine levels, sepsis-related down-regulation of major histocompatibility complex II and CD14 expression on leukocytes, bacterial translocation, and endotoxemia related to the increasing intensity of the treatment provided.…”
Section: Clearance Of Infl Ammatory Mediators and Immunomodulationmentioning
confidence: 66%
“…After the shock condition, however, when the vasoactive agents were added in the gentisic septic group and the NE septic group, there were increases in afterload which led to increases in Pwp. While intravenous fluids could easily be given when the Pwp was low, we did not want to phlebotomize that animal if the Pwp rose, because hemodynamic instability often follows this procedure [ 33 ]. Overall, however, the changes in Pwp were relatively small (see Table 3 ), and moreover, we do not think these changes would affect the hemodynamic findings to a significant extent.…”
Section: Discussionmentioning
confidence: 99%